The Effect of Organizational Innovation and Organizational Learning on Organizational Performance - MOHAMMAD DAUD ALI; DR. SYED IMAD SHAH; DR. SHAHID JAN; MUHAMMAD ILYAS (Journal of Business & Tourism, 2021)
This research tries to investigate the influence of organizational learning on innovation on one hand and the impact of innovation on performance on the other. Upon the review of literature, two hypotheses projected in pursuit of the research: the positive impact of organizational learning on innovation as well as the co relational effect of innovation with performance. Data was obtained distributing questionnaires in five public sector universities of Peshawar, Khyber Pakhtunkhwa, Pakistan. Conclusions substantiate hypotheses thus provided additional substantiation that organizational learning has a say in innovation capacity, and also the fact that innovation is positively associated to organization learning (R2 = 0.65) and coefficient β is 0.31 this clearly show that innovation leads to organization learning, on the other hand organization learning has positively associated to organization performance (R2 = 0.70) and coefficient β is 0.54 this means that organization learning leads to organization performance, and has positive significant effect on financial performance